Pemanfaatan Alat Peraga Matematika Kotak Perkalian Dalam Meningkatan Minat Belajar Numerasi Di Sanggar Belajar Kampung Bharu Malaysia - Simamora, Suryani Parningotan; Sari, Suci perwita; Nasution, Ismail Saleh; Saragih, Mandra; Nasution, Dewi Kesuma; Syamsuyurnita, Syamsuyurnita (Peneliti.net, 2023)
Numeration is the ability to apply the concept of numbers and mathematical operations in everyday life. Such research is a qualitative descriptive method with case studies. Data collection techniques are interviews, observation and documentation. Many students still do not understand arithmetic. things. This is because students are less trained in various things in the form of arithmetic. It could also be one of the causes of the low numeracy skills of Grade 4 students at the Guidance Center of Kampung Bharu Malaysia. Students need to understand multiplication learning because it is needed in everyday life. As a teacher, it is therefore important to apply what you have learned to numbering at a minimum: one day and one hour to add up the number of students. This being an important reason for teachers to innovate learning to count means being a facilitator and observer, from teacher to student. user, developer, and maker; The teacher's innovation process in the three stages of learning to count through: introductory concepts, transitions/stages and symbol stages; and the impact of teacher innovation. The multiplication box learning method to increase logical-mathematical intelligence in the sense of logical thinking, can add storage, can categorize, can add numbers, can learn to act, to become a problem solver, to understand cause and effect and to be able to do it to increase accuracy. (1) this environment includes aspects such as: interesting, fun and increases student creativity (2) The quality of quantitative media in learning Visual Figures is